2022
DOI: 10.1186/s12916-022-02558-z
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity and mechanism of the antifungal drug, anidulafungin, suggesting its potential to promote treatment of viral diseases

Abstract: Background The severe fever with thrombocytopenia syndrome disease (SFTS), caused by the novel tick-borne SFTS virus (SFTSV), was listed among the top 10 priority infectious disease by World Health Organization due to the high fatality rate of 5–30% and the lack of effective antiviral drugs and vaccines and therefore raised the urgent need to develop effective anti-SFTSV drugs to improve disease treatment. Methods The antiviral drugs to inhibit SFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…This suggests the potential of antifungals with common pharmacological features to have anti-HBV activities. The antiviral effects of some antifungals are shown before [26,35], indicating the potential ancestry druggable site shared in viruses and fungi that opens a vast field in the future researches.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the potential of antifungals with common pharmacological features to have anti-HBV activities. The antiviral effects of some antifungals are shown before [26,35], indicating the potential ancestry druggable site shared in viruses and fungi that opens a vast field in the future researches.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated that HRTV (along with other viruses) was inhibited by anidulafungin in a dose-dependent manner by interfering with the virus’s entry into cells. Anidulafungin is approved by the FDA for antifungal use [ 69 ].…”
Section: Potential Treatments For Hrtv Infectionmentioning
confidence: 99%
“…Liver, spleen, lungs, and kidneys were collected from mice infected with the HBGS13 strain on days 4 and 12 p.i. (n = 3 at each time point), respectively, and were fixed in 4% paraformaldehyde for 24 h. Hematoxylin-eosin (H&E) staining and immunohistochemical assays were performed to observe the pathological changes caused by SFTSV infection and to blot SFTSV infection in tissues using a pAb against SFTSV NP as previously described [29]. SFTSV RNA loads in tissues and serum samples were determined by qRT-PCR as previously showed [30].…”
Section: Animal Experimentsmentioning
confidence: 99%